Counselling Psychology and Psychophysiology: The Neglected Interface - Robinson, John W.; Kaplan, Bonnie J. (Canadian Journal of Counselling and Psychotherapy, 2011)
The purpose of this article is to encourage more frequent use of psychophysiological methods and psychophysiological perspectives in counselling research. Three questions are addressed: how counselling psychology has been studied up to now using psychophysiological methods, which psychophysiological methods may prove useful for future research, and what are some important questions to be answered using these methods.